PERANAN POLISI SEKTOR DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN MINUMAN KERAS DI KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - ROHSULANA, PRATUCHA WASTU (Dinamika Hukum, 2017)
The purpose of this study is to analyze the role of Police Sector in the effort ofprevention and prevention of liquor in Kecamatan Polokarto Sukoharjo Districtand analyze the factors that inhibit the handling of liquor.The backdrop of the study that alcohol abuse by consuming it beyond the limits offairness, in addition will be an individual problem that can harm yourself, inaddition to the wider problem can be a problem for the community.The research method consisted of sociological juridical research type, descriptiveresearch characteristic. The data needed are primary and secondary data, whiledata analysis is done qualitatively.The result of the research shows that the role of Sukoharjo Polokarto PoliceSector in overcoming the violation of alcohol is done by preventive means such asgiving counseling about the danger of liquor, giving counseling about narcoticsand dangerous drugs and liquor in schools. In addition to perform routine patrolsevery day at certain hours. Another effort is to follow up any community reportson information about cases related to liquor or other cases. Always ready to assistthe community in all actions concerning community ills. Inhibiting factors are thelack of public awareness of the dangers of liquor as well as reports or complaintsfrom the community that are sometimes unclear so that the follow-up processbecomes impeded, the level of community education is still low. easy access toliquor, extensive operation of Polokarto Police Patrol and the lack of personnel inPolokarto Police Sector.Keywords: Polokarto Police Sector Roles, Countermeasures of Liquor